Nonsmall cell lung cancer from HIV-infected patients expressed programmed cell death-ligand 1 with marked inflammatory infiltrates. (20th February 2018) - Domblides, Charlotte; Antoine, Martine; Hamard, Cécile; Rabbe, Nathalie; Rodenas, Anita; Vieira, Thibault; Crequit, Perrine; Cadranel, Jacques; Lavolé, Armelle; Wislez, Marie
Abstract : Objective: Immunotherapies targeting the programmed cell death-1 (PD-1)/PD-ligand 1 (PD-L1) checkpoint improved prognosis in lung cancer. PD-1/PD-L1 status, however, has not been investigated in human immunodeficiency virus (HIV)-positive patients. This study assessed PD-L1 status and tumor immune-cell infiltration in nonsmall cell lung cancer (NSCLC) in HIV patients. Methods: Consecutive HIV patients treated between 1996 and 2014 were enrolled. PD-L1 tumor expression was assessed using immunohistochemistry with two antibodies (clones 5H1 and E1L3N), and tumor immune-cell infiltration with CD3, CD4, CD8, CD20, CD163, and MPO. PD-L1 expression and immune infiltration results were compared with those of 54 NSCLCs from unknown HIV status patients. Results: Thirty-four HIV-positive patients were evaluated: predominantly men (88.2%) (median age: 51.1 years) presenting stage IV (38.2%) adenocarcinomas (76.5%). The median blood CD4 + count was 480 cells/μL (86–1120) and 64% exhibited undetectable viral load. The PD-L1 score (percentage of positive cells × intensity) was higher in HIV-positive than HIV-undetermined patients with the E1L3N clone [median (range) 0 (0–150) versus 0 (0–26.7), P  = 0.047], yet not with the 5H1 clone [0 (0–120) versus 0 (0–26.7) P  = 0.07, respectively]. PD-L1 expression frequency did not differ between both cohorts (18.7 versus 9.3% using E1L3N and 10 versus 5.6% using 5H1 clone, respectively). There were significantly greater cytotoxic T-cell ( P  < 0.001), B-lymphocyte ( P  = 0.005), and activated macrophage ( P  < 0.001) infiltrations in the HIV-positive patients, but no differences for CD4 + T cells. Conclusion: Tumors in HIV-positive patients seem to express higher PD-L1 levels with increased immune infiltration, supporting their inclusion in clinical trials assessing immune checkpoint inhibitors. Abstract : Supplemental Digital Content is available in the text